Effectivity of the jackfruit leaves infusion (Artocarpus heterophyllus l.) as a larvacide to the mortality rate of Aedes aegypti larva - Fina Alvia Rahma; Endang Mahati; R.A. Kisdjamiatun RMD; Ryan Halleyantoro (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Larval stage control using temephos, a chemical larvicide powder, was not completely safe. WHO recommended to use biological controls. Jackfruit leaves which contain saponins, flavonoids, and tannins can be used as alternate. This study was conducted to determine the effectivity of jackfruit leaves (Artocarpus heterophyllus L.) infusion on the mortality of Aedes aegypti larvae using post test only control group design. 600 of Aedes aegypti larvae were divided into 1 control group and 5 experiment groups that consist  jackfruit leaves infusion concentrations of 4%, 8%, 12%, 16%, 20% with four times replication. The mortality of larvae was observed every 8 hours to 48 hours. The LC50 and LT50 were obtained by probit analysis were 3.842% and 2.150 hours. In the repeated Kruskal-Wallis test and Mann-Whitney, there were significant differences (p<0.05) in the mortality of Aedes aegypti larvae that died based on differences in the concentration of jackfruit leaf infusion. In the Spearman test, there were significant correlations (p<0.05) between the concentration of jackfruit leaves infusion and the mortality of Aedes aegypti larvae and the death rate of Aedes aegypti larvae. The results of the study are expected to be alternatives to chemical larvicides commonly used by the community.